Rare Upper Airway Anomalies. (January 2016) - Windsor, Alanna; Clemmens, Clarice; Jacobs, Ian N.
Summary: A broad spectrum of congenital upper airway anomalies can occur as a result of errors during embryologic development. In this review, we will describe the clinical presentation, diagnosis, and management strategies for a few select, rare congenital malformations of this system. The diagnostic tools used in workup of these disorders range from prenatal tests to radiological imaging, swallowing evaluations, indirect or direct laryngoscopy, and rigid bronchoscopy. While these congenital defects can occur in isolation, they are often associated with disorders of other organ systems or may present as part of a syndrome. Therefore workup and treatment planning for patients with these disorders often involves a team of multiple specialists, including paediatricians, otolaryngologists, pulmonologists, speech pathologists, gastroenterologists, and geneticists.